Resolução anafórica em português europeu L2: efeitos de animacidade e a posição do antecedente - Teixeira, Joana; Fiéis, Alexandra; Madeira, Ana (Revista da Associação Portuguesa de Linguística, 2021)
This study investigates the interpretation of subject pronouns in L2 EP by Italian native speakers, to examine the following questions: In overt subject resolution, do L1 Italian - L2 European Portuguese learners behave like L1 EP speakers regarding antecedent animacy (a property at the syntax-semantics interface) at L2 developmental stages and at the near-native level?; When the antecedent in object position is animate, do L1 Italian - L2 EP learners exhibit permanent optionality in the interpretation of overt subject pronouns but not of null subjects, as claimed by Sorace (2016), a.o.? Participants were 15 adult EP native speakers, 10 intermediate, 10 advanced and 10 near-native Italian adult learners of L2 EP. They were administered two multiple-choice tasks (speeded and untimed) with a 2x2 design crossing the following variables: animacy of the matrix object (animate vs. inanimate) and type of embedded pronominal subject (overt vs. null). Results indicate that L2 learners show problems only in the areas where the L1 and the L2 differ (Madeira, Fiéis & Teixeira, this volume), namely: the resolution of overt subjects in the presence of [-animate] object antecedent and the resolution of null subjects. Learners’ performance in these areas remains unstable even at the near-native level. These findings challenge the ideas that internal interfaces (syntax/semantics) are not persistently problematic and that null subjects are unproblematic in L2 anaphora resolution (cf. Sorace, 2011, 2016). They moreover point to the importance of L1 influence in L2 anaphora resolution, a factor generally played down in previous studies (e.g., Sorace, 2016).